2015
DOI: 10.1051/0004-6361/201425361
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of coupling between the thermal and nonthermal emission in the gamma-ray binary LS I +61 303

Abstract: The gamma-ray binary LS I +61 303 is composed of a Be star and a compact companion orbiting in an eccentric orbit. Variable flux modulated with the orbital period of ∼26.5 d has been detected from radio to very high-energy gamma rays. In addition, the system presents a superorbital variability of the phase and amplitude of the radio outbursts with a period of ∼4.6 yr. We present optical photometric observations of LS I +61 303 spanning ∼1.5 yr and contemporaneous Hα equivalent width (EW Hα ) data. The optical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
6
30
0
Order By: Relevance
“…These timescales are usually interpreted as the orbital and superorbital periods of the system (see, however, Massi & Jaron (2013); Massi, Jaron & Hovatta (2015)). The detection of similar periods has been recently reported in the optical (Zamanov et al 2013;Paredes-Fortuny et al 2015), X-ray (Chernyakova et al 2012;Li, Torres & Zhang 2014) and gamma-ray bands (Ackermann et al 2013;Jaron & Massi 2014).…”
Section: Introductionsupporting
confidence: 79%
“…These timescales are usually interpreted as the orbital and superorbital periods of the system (see, however, Massi & Jaron (2013); Massi, Jaron & Hovatta (2015)). The detection of similar periods has been recently reported in the optical (Zamanov et al 2013;Paredes-Fortuny et al 2015), X-ray (Chernyakova et al 2012;Li, Torres & Zhang 2014) and gamma-ray bands (Ackermann et al 2013;Jaron & Massi 2014).…”
Section: Introductionsupporting
confidence: 79%
“…Moreover, Paredes-Fortuny et al (2015) discovered that the orbital phase shift also affects the variations in the equivalent width (EW) of the Hα emission line from LS I +61 • 303. The orbital phase shift (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…The first method finds the two physical periods directly, and the second method deals with the result of the beating. In addition to radio data, the periods P 1 and P 2 were also directly determined in the LombScargle spectrum of data at apastron for Fermi-LAT data (Jaron & Massi 2014) and X-ray data (D'Aì et al 2016), whereas the long-term modulation (Zamanov et al 2013) and orbital shift (Paredes-Fortuny et al 2015) were found in the equivalent width EW of the Hα emission line.…”
Section: Beating Between Orbit (P 1 ) and Precession (P 2 )mentioning
confidence: 99%